2017
DOI: 10.3847/2041-8213/aa5f50
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric Multiscale Observations of Electron Vortex Magnetic Hole in the Turbulent Magnetosheath Plasma

Abstract: We report the observations of an electron vortex magnetic hole corresponding to a new type of coherent structures in the magnetosheath turbulent plasma using the Magnetospheric Multiscale (MMS) mission data. The magnetic hole is characterized by a magnetic depression, a density peak, a total electron temperature increase (with a parallel temperature decrease but a perpendicular temperature increase), and strong currents carried by the electrons. The current has a dip in the center of the magnetic hole and a pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
113
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 104 publications
(128 citation statements)
references
References 59 publications
15
113
0
Order By: Relevance
“…Kinetic‐scale magnetic dips (KSMDs) are a significant depression of magnetic field strength with a scale size close to or less than a proton gyroradius (ρ i ). These structures have been observed both in the Earth's magnetospheric plasma sheet (e.g., Ge et al, ; Gershman et al, ; Goodrich et al, ; Sun et al, ; Sundberg et al, ; Yao et al, ; Zhima et al, ; Zhang et al, ) and magnetosheath (e.g., Huang, Sahraoui, et al, ; Yao et al, ). In addition to observational investigations, KSMDs have also been extensively studied through theoretical analysis and numerical simulations (e.g., Balikhin et al, ; Haynes et al, ; Ji et al, ; Li et al, ; Roytershteyn et al, ).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Kinetic‐scale magnetic dips (KSMDs) are a significant depression of magnetic field strength with a scale size close to or less than a proton gyroradius (ρ i ). These structures have been observed both in the Earth's magnetospheric plasma sheet (e.g., Ge et al, ; Gershman et al, ; Goodrich et al, ; Sun et al, ; Sundberg et al, ; Yao et al, ; Zhima et al, ; Zhang et al, ) and magnetosheath (e.g., Huang, Sahraoui, et al, ; Yao et al, ). In addition to observational investigations, KSMDs have also been extensively studied through theoretical analysis and numerical simulations (e.g., Balikhin et al, ; Haynes et al, ; Ji et al, ; Li et al, ; Roytershteyn et al, ).…”
Section: Introductionmentioning
confidence: 94%
“…Many of these key processes involve kinetic‐scale physics. With measurements of high‐temporal cadence from the Magnetospheric Multiscale (MMS) mission (Burch et al, 2016), the KSMDs and some possible related structures were reported in the turbulent magnetosheath (Huang, Sahraoui, et al, ; Yao et al, ; Yao, Shi, Guo, et al, ) and are thought to play an important role in dissipating energy (Huang, Sahraoui, et al, ). In addition, from recent two‐ and three‐dimensional particle‐in‐cell simulations, the KSMDs were found in turbulent magnetized plasmas (Haynes et al, ; Roytershteyn et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The electron vortex is reminiscent of small‐scale magnetic holes, observed extensively in the plasma sheet (Gershman et al, ; Goodrich, Ergun, & Stawarz, ; Goodrich, Ergun, Wilder, et al, ), magnetosheath (Huang, Du, et al, ; Huang, Sahraoui, et al, ; Yao et al, ), and kinetic simulations (Haynes et al, ). In these structures, electron‐scale current loops generate depletions in | B |, and similar to the structure observed here, J in some cases is linked to electron E × B drifts (Goodrich, Ergun, & Stawarz, ).…”
Section: Small‐scale Substructurementioning
confidence: 99%
“…The spacecraft separation is about 10–20 km, capable of resolving the vorticity of ion‐scale and larger‐scale structures. Such configuration, however, may not measure the vorticity of electron‐scale vortex such as in Huang et al (, ) and Zhong et al ().…”
Section: Observation and Analysismentioning
confidence: 99%